Cartas Celestes XIV (Celestial Maps XIV) by Almeida Prado - Fregoneze, Carmen Celia (Música em Perspectiva, 2012)
This paper discusses the work for piano “Cartas Celestes XIV”, by Almeida Prado. The aim of this study is to analyse the musical and technical demands of the piece as a means to help the piano performance.